Basic Concepts and Definitions in Educational Robotics (Eurasian Scientific Herald, 2024)
This article provides an overview of the basic concepts and definitions in educational robotics. The article provides examples of the use of basic concepts in practical training, and also discusses trends and prospects for the development of educational robotics. The results obtained can be useful both for researchers and teachers, and for practitioners in the field of educational technologies and robotics.